KONSEP ISLAMISASI ILMU ISMAIL RAJI AL FARUQI DAN RELEVANSINYA DENGAN SISTEM PENDIDIKAN NASIONAL - Al Arifi, Nasiruddin (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
This study is motivated by the tension between secular modern science and Islamic spiritual values, which, according to Ismail Raji al Faruqi, has led to an epistemological crisis in the Muslim world. The primary objective of this research is to explore al Faruqi’s concept of the Islamization of knowledge and its relevance to Indonesia’s national education system. This research employs a qualitative method with a thematic approach, using content analysis of al Faruqi’s seminal work Islamization of Knowledge: General Principles and Work Plan and related documentation. The findings reveal that al Faruqi’s concept is rooted in the principle of tawhid (the unity of God), encompassing five unities—God, creation, truth, life, and humanity—and operationalized through twelve strategic steps to reconstruct modern disciplines within an Islamic framework. This concept aligns with the goals of the national education system in promoting religious values and human development, though it differs in its literal epistemological approach